Effect of synbiotic supplementation on growth, immunity and intestinal morphometry of broiler chickens in summer season - Sethy, Kamdev (The Indian Journal of Animal Sciences, 2026)
To ascertain the effect of synbiotic supplementation on growth, immunity and intestinal morphometry in broiler chicken during summer season, one hundred sixty-day old Vencobb chicks were randomly allocated into five treatments. Each treatment has 32 birds consisting 4 replicates of 8 birds each. T0: Basal diet; T1: Basal diet + AGP (Salinomycin); T2: Basal diet + prebiotic [Mannan oligosaccharides (MOS)]; T3: Basal diet + probiotic (Lactoplus) and T4: Basal diet+ symbiotic (MOS + Lactoplus). The birds were reared in three phases: pre starter phase (0-1 wk), starter phase (2-3 wks) and finisher phase (4-5 wks) and fed as per BIS (2007). The experiment was continued for the period of 35 days. Gain in body weight, FCR, immunity, morphometry of intestine and histology of liver and kidney was studied. There was significant effect on body weight and FCR following the supplementation of synbiotic. The antibody titre against Ranikhet disease vaccine and the CBH reaction against PHA-P was much greater (p